Effectiveness of online purchasing attributes on company performance: a case of Telone Zimbabwe - Mutemararo, Ashley (Midlands State University, 2017)
There is stiff competition in the telecommunication sector where companies are coming up with brilliant ideas in order to fight the competitive world. The purpose of the research was to investigate the effectiveness of online purchasing attributes on company performance. A case study on Telone Zimbabwe. The purpose of the research were to find out the impact of web quality on customer loyalty, to determine the effectiveness of e-payment system on sales volume and to determine the effect of online retailing on market share. Research questions further explained the research objectives. Literature review was conducted to know what exactly various authors explained about the research objectives which was answering the research questions. These different authors were highlighted their views so as to get a deeper understanding theoretically. The findings from Gallego et al (2015), Mohd and Tahir (2009) and Jiradilok et al (2014) covered website quality, consumer purchase intention, customer satisfaction, e- commerce and sales volume. In addition of what the researchers looked at, the researcher wants to research on web quality, e-payment system and online retailing basing with a telecommunication company in Zimbabwe on the topic entitled the effectiveness of online purchasing attributes on company performance. A case study of Telone Zimbabwe. Descriptive research design and exploratory research design were used. Questionnaires were distributed to collect data from consumers and the questionnaire made use of a five-point Likert scale in order to rate the effectiveness of web quality, e-payment system and online retailing. Interviews were undertaken of employees and management. The results showed that website quality has an influence on customer loyalty, electronic payment system types has an effect to sales volume and online retailing also has an effect on market share. The results showed that there is an influence in purchasing online and has contributed to the revenue of Telone Zimbabwe. It was evidenced from the study that online purchasing has an influence on company performance. It was recommended that Telone must cultivate its customer relationships to know what customers want on the website and be innovative to have a better website. It was also recommended that Telone must have online sales promotions on voice to boost e-payments. Failure to utilize online purchasing in this era of technology will result in the organization underperforming.